Regional Autonomy and Development in South Sumatra - Djunaidi, Djunaidi (Graduate Program Magister Manajemen Pendidikan, 2023)
This study aims to describe regional autonomy and development in South Sumatra. Community development is a process of change for the better, covering all aspects of people’s lives to improve material and mental well-being, as well as physical and psychological well-being. Regional autonomy provides broad opportunities for regions to develop their regions in accordance with the circumstances or conditions and aspirations of the local community. This research includes a literature review that discusses 1) autonomy accelerating regional development in South Sumatra which is related to infrastructure development in South Sumatra Province discussed in the coordination meeting, namely the progress of the Toll Road, namely Kayu Agung-Palembang-Betung, Kramasan (Palembang)-Musi Landas-Betung section. Sekayu-Tempino-Jambi Intersection, Indralaya-Muara Enim Intersection, Railways and Ports namely the Logistics Train, Lahat-Muara Enim-Prabumulih-Kertapati (Palembang) double track. 2) Regional development is a symbol of progress in South Sumatra, discussing regional development in South Sumatra as a symbol of success which is marked by several awards given to the province of South Sumatra. The Governor of South Sumatra has received regional autonomy and development awards several times.